First recording and molecular diagnostics of three ascomycetous macrofungi from Nineveh, Iraq - Jarjees, Rawaa Mohammed; Abdul-Hadi, Shimal Younis; Al-Khesraji, Talib Owaid (Journal of Advanced Education and Sciences, 2023)
This research project has referred to three of macrofungi (Ascomycota): Geopora foliacea, Helvella leucopus and Peziza vesiculosa. The first two types of macrofungi have been collected from Al- Nimrud area، While the third type (Peziza vesiculosa) was collected from Mosul Dam northern of Mosul. The samples were diagnosed phenotypically and microscopically, as their morphological and microscopic characteristics were determined. Moreover, the samples were molecularly identified by DNA sequencing data. These macrofungal species are recorded for the first time from Iraq.